Un tipo intermedio di Stato tra l'unitario e il federale caratterizzato dall'autonomia regionale (TEST Antologia di Diritto Pubblico, 2024)
The Author argues that the system of regional autonomy gives rise to the establishment of a type of state different from the unitary and federal. Demonstrating the assumption, differentiating the concept of "decentralization" from that of "autonomy", and on the basis of the constitutions of the ceased Austrian monarchy and the current Spanish republic, the Author highlights how "autonomous regions" differ from both the "provinces" of the unitary state and the "member states" of the federal state.